iPS-cell technology and the problem of genetic instability—can it ever be safe for clinical use? - Attwood, SW; Edel, MJ (MDPI, 2019)
The use of induced Pluripotent Stem Cells (iPSC) as a source of autologous tissues shows great promise in regenerative medicine. Nevertheless, several major challenges remain to be addressed before iPSC-derived cells can be used in therapy, and experience of their clinical use is extremely limited. In this review, the factors affecting the safe translation of iPSC to the clinic are considered, together with an account of efforts being made to overcome these issues. The review draws upon experiences with pluripotent stem-cell therapeutics, including clinical trials involving human embryonic stem cells and the widely transplanted mesenchymal stem cells. The discussion covers concerns relating to: (i) the reprogramming process; (ii) the detection and removal of incompletely differentiated and pluripotent cells from the resulting medicinal products; and (iii) genomic and epigenetic changes, and the evolutionary and selective processes occurring during culture expansion, associated with production of iPSC-therapeutics. In addition, (iv) methods for the practical culture-at-scale and standardization required for routine clinical use are considered. Finally, (v) the potential of iPSC in the treatment of human disease is evaluated in the light of what is known about the reprogramming process, the behavior of cells in culture, and the performance of iPSC in pre-clinical studies.